Organizational Culture and Work Stress as Determinants of Employee Job Satisfaction - Shabrina Anjarany; Maria Merry Marianti (Penerbit Goodwood, 2026)
Purpose: This study aimed to examine the extent to which employees’ job satisfaction at Bank Sumedang is influenced by organizational culture and the level of work stress experienced. Research Methodology: This study gathered data through a survey of 121 full-time employees who had been employed for over one year, and the analysis of variable relationships was conducted using Structural Equation Modeling (SEM). Results: The analysis indicates that organizational culture contributes positively and significantly to job satisfaction, in contrast to work stress, which has a negative but non-significant relationship with job satisfaction. Conclusions: This study concludes that fostering a strong organizational culture is a more critical lever for enhancing employee job satisfaction at Bank Sumedang than managing work stress, which shows a non-significant impact. Limitations: This study is limited to a single institution, namely Bank Sumedang; therefore, the generalization of the findings to other organizations with different characteristics should be approached with caution. Contributions: This study provides practical contributions to Bank Sumedang’s management in formulating human resource management strategies, emphasizing the importance of fostering a strong organizational culture and implementing effective stress management systems to improve employee job satisfaction.